2022
DOI: 10.7150/jca.65145
|View full text |Cite
|
Sign up to set email alerts
|

Low PARP-1 expression level is an indicator of poor prognosis in patients with stage II and III gastric cancer

Abstract: Purpose: This study aimed to investigate the relationship between DNA damage response (DDR) related protein expression and clinical outcomes of patients with stage II and III gastric cancer undergoing gastrectomy. Materials and Methods: From January 2005 to December 2017, 217 gastrectomized patients with stage II and III gastric cancer were analyzed for disease-free and overall survival (DFS and OS, respectively) based on their DDR expression status. We performed the immunohistochemical assessment of MLH1, MSH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…Patients who underwent surgery and whose tumors showed low expression of PARP-1 exhibited a shorter overall survival than that of those with high expression. This retrospective study suggested that PARP-1 expression could be of prognostic value in select solid tumor models [73]. Other studies of PARP expression in locally advanced breast cancer and pancreatic cancer also reported that low expression of PARP-1 was associated with poor prognosis [74,75].…”
Section: Poly (Adp-ribose) Polymerase (Parp)mentioning
confidence: 67%
“…Patients who underwent surgery and whose tumors showed low expression of PARP-1 exhibited a shorter overall survival than that of those with high expression. This retrospective study suggested that PARP-1 expression could be of prognostic value in select solid tumor models [73]. Other studies of PARP expression in locally advanced breast cancer and pancreatic cancer also reported that low expression of PARP-1 was associated with poor prognosis [74,75].…”
Section: Poly (Adp-ribose) Polymerase (Parp)mentioning
confidence: 67%
“…Elevated expression levels of miR-203, miR-218, and miR-194 have been correlated with a favorable prognosis for gastric cancer, while diminished expression of miR-17-5p and miR-34a serves as a marker for an unfavorable prognosis ( 6 , 20 , 21 ). Furthermore, a diminished expression of PARP-1, a DNA damage response (DDR)-associated protein, has been identified as a prognostic indicator for patients with stage 2 and 3 gastric cancer ( 22 ). Given its role as a DDR-associated gene, the low expression of MSH2 may similarly contribute to an unfavorable prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…PARP1 inhibition was found to be effective in the treatment of tumors carrying mutations in BRCA1/2 genes exploiting the concept of synthetic lethality [ 85 ]. PARP1 is mostly over-expressed in cancers [ 86 ], but in the work [ 87 ] low PARP1 expression level was found in the clinical samples from the patients with gastric cancer. The inhibition of PARP1 activity could sensitize tumor cells to the action of chemotherapeutic drugs.…”
Section: Discussionmentioning
confidence: 99%